Avoiding the rating bounce: Why rating agencies are slow to react to new information - Gunter Löffler (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2002)
Rating agencies state that they take a rating action only when it is unlikely to be reversed shortly afterwards. Based on a formal representation of the rating process, I show that such a policy provides a good explanation for the empirical evidence: Rating changes occur relatively seldom, exhibit serial dependence, and lag changes in the issuers' default risk. In terms of informational losses, avoiding rating reversals can be more harmful than monitoring credit quality only twice per year.
urn:nbn:de:hebis:30-18005
Keywords: G2; G21; 330; conservatism; credit rating; rating agencies; rating migration; Kreditwürdigkeit; Informationsverhalten; Kreditrisiko; Schätzung; Theorie; Welt